Individual and collective identification in contemporary forensics - Cole, Simon (2018)
It has long been understood that individual and collective identification are inexorably intertwined. This convergence is not limited to genetics. This paper discusses the convergence of individual and collective identification in a comparative analysis of three other forensic areas: fingerprint analysis, microscopic hair comparison, and microbiome forensics. In all three case studies, we see purportedly individualizing technologies reverting, in a sense, to collective identification. Presumably, this has much to do with the perceived utility of collective identification. When knowing precisely who is the donor of a trace is not possible, or not useful, then knowing that the donor is ‘white,’ or ‘black,’ or ‘Middle Eastern’ begins to seem somehow useful. In each case, we also see that these collective identifications are ultimately founded on crude and broad, seemingly ‘commonsensical’ or ‘social,’ racial categories. These categories, meanwhile, are based on a less-than-fully-transparent combination of self-identification or official ascription. These suspect data are then transformed into seemingly persuasive scientific claims about the genetic attributes of this or that ‘race,’ ‘ethnicity,’ or ‘ancestry.’ Through this comparison the paper will explore how the individual and the collective are ‘done’ differently and similarly in different forensic disciplines